Bacterioruberin and salinixanthin carotenoids of extremely halophilic Archaea and Bacteria: a Raman spectroscopic study - Jehlička, J; Edwards, H G M; Oren, A (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2013)
Laboratory cultures of a number of red extremely halophilic Archaea (Halobacterium salinarum strains NRC-1 and R1, Halorubrum sodomense, Haloarcula valismortis) and of Salinibacter ruber, a red extremely halophilic member of the Bacteria, have been investigated by Raman spectroscopy using 514.5nm excitation to characterize their carotenoids. The 50-carbon carotenoid α-bacterioruberin was detected as the major carotenoid in all archaeal strains. Raman spectroscopy also detected bacterioruberin as the main pigment in a red pellet of cells collected from a saltern crystallizer pond. Salinibacter contains the C40-carotenoid acyl glycoside salinixanthin (all-E, 2'S)-2'-hydroxy-1'-[6-O-(methyltetradecanoyl)-β-d-glycopyranosyloxy]-3',4'-didehydro-1',2'-dihydro-β,ψ-carotene-4-one), for which the Raman bands assignments of are given here for the first time.
Keywords: Haloarcula; glykosidy; Halorubrum; Halobacteriaceae; Glycosides; Bacteroidetes; Halobacterium salinarum; Carotenoids; karotenoidy; Spectrum Analysis, Raman; Ramanova spektroskopie